2020
DOI: 10.1080/1478422x.2020.1772587
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated corrosion of pipeline steel under dynamic DC stray current interference

Abstract: In this paper, the statistical analysis of fluctuation characteristics of pipeline potential under dynamic DC stray current interference was carried out based on field test data. Then a self-designed experimental set-up was applied to study the corrosion behaviour of X70 steel in soil-simulating conditions. The statistical results showed that under the dynamic DC stray current interference, the pipeline potential was periodically fluctuated with dynamic periods between 10 and 300 s. The laboratory experiment r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The potential of the inflow point of stray current is negative, which can cause the outer corrosion protection layer to peel off when it is serious, and the potential of the outflow point is usually higher than the protection potential, resulting in local electrochemical corrosion of the pipeline. It is an effective way to reduce the interference of stray current by measuring the protection potential of buried pipeline and evaluating the impact on cathodic protection [4][5][6][7]. In this paper, the corrosion behavior of buried steel pipes under DC interference under cathodic protection is studied to explore the effectiveness of cathodic protection system under different circumstances, which is conducive to accurately judging the stray current corrosion problem of buried metal pipes in engineering, improving the effectiveness of cathodic protection system, and formulating reasonable evaluation criteria for stray current corrosion and cathodic protection.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of the inflow point of stray current is negative, which can cause the outer corrosion protection layer to peel off when it is serious, and the potential of the outflow point is usually higher than the protection potential, resulting in local electrochemical corrosion of the pipeline. It is an effective way to reduce the interference of stray current by measuring the protection potential of buried pipeline and evaluating the impact on cathodic protection [4][5][6][7]. In this paper, the corrosion behavior of buried steel pipes under DC interference under cathodic protection is studied to explore the effectiveness of cathodic protection system under different circumstances, which is conducive to accurately judging the stray current corrosion problem of buried metal pipes in engineering, improving the effectiveness of cathodic protection system, and formulating reasonable evaluation criteria for stray current corrosion and cathodic protection.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the facilities that were equipped with the ground electrode can be regarded as interference source with different characteristics. Some of the DC interferences are periodically fluctuated in minutes [23]. Some of the directions of the DC currents are changed with the period time of the train moving direction [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies have shown that stray currents can cause potential shifts and can lead to cathodic protection (CP) failures, which indirectly accelerate corrosion [11,15]. Qin et al [16] found that the potential of X70 steel would periodically fluctuate in soil under a dynamic DC interference. Wang [17] also reported the potential of Q235 steel to shift positively under DC interference, while the corrosion rate increased with the current density.…”
Section: Introductionmentioning
confidence: 99%